Humāẏuna Āhamedera upanyāse muktiyuddha - Āktāra, Āpharojā (Pratibhā Prakāśa, 2022)
Study on the depiction of 1971 liberation of Bangladesh in the novels of Humāẏūna Āhameda, 1948-2012, Bengali author.
Literaturverzeichnis: Seite 164-168
Keywords: Āhameda; Humāẏūna; 1948-2012; Fictional works.; Bangladesh; History; Revolution; 1971; Literature and the revolution.